TIME TO ASSESS LEARNING OUTCOMES: TALOE WEBTOOL APPLICATIONS - Alfredo Soeiro (2018)
This paper is placed in the intersection of these three fields: learning outcomes, assessment of students learning and learning. The purpose of this study is to contribute to accrediting learning as an assessment delivery tool that can be applied independently of the learning pathways. It intends to contribute to the achievement of recognition and mobility of students and to the creation of a flexible Education System. In general terms, the approach chosen was to develop a model that matches specific assessment methods to measure the achievement of the learning outcomes (LO). Again in general terms, this means that it could be possible for a teacher to define the LO of hers/his online course and from this definition to have an indication of the assessment methods she/he might consider using. Formally, this problem is defined as To what extent assessment methods may be used to measure intended the achievement of LO in education?